Binuclear ruthenium(II) complexes of 4, 4′-azopyridine bridging ligand as anticancer agents: synthesis, characterization, and in vitro cytotoxicity studies. Issue 16 (18th August 2019) - Khanvilkar, Priyanka; Pulipaka, Ramadevi; Shirsath, Kavita; Devkar, Ranjitsinh; Chakraborty, Debjani
Abstract: Four new binuclear Ru(II)-arene complexes with N-ferrocenyl amino acid ligands and 4, 4′-azopyridine as the bridging group [(p-cym)(Fc-AA)Ru(μ-azpy)Ru(Fc-AA)(p-cym)]Cl (C1 –C4 ; where p-cym = p-cymene, MeC6 H4 Pr i ; Fc-AA = N-ferrocenyl amino acid conjugate ligands (Fc-tyr 1, Fc-phe 2, Fc-leu 3, Fc-trp 4 ) and azpy = 4, 4′-azopyridine) were synthesized and characterized by 1 H NMR, UV—visible, FTIR and mass spectroscopy, and CHN analysis. The structure of one of the precursor mononuclear complexes, [(p-cym)Ru(Fc-phe)Cl], was determined by single-crystal X-ray diffraction studies. Binding of the complexes with calf-thymus DNA and bovine serum albumin (BSA) has been evaluated using absorption and emission spectral studies. Ethidium bromide-displacement studies and DNA-viscosity measurements affirmed intercalative interaction mode between complexes and CT-DNA. Fluorescence titration was used to explore interaction of the complexes with BSA. MTT assay was adopted to evaluate the anticancer activity of C1 –C4 on HeLa cell line and the corresponding IC50 values were calculated. The IC50 values of the complexes were higher than that for cisplatin but much lower than for NAMIA and RAPTA-C. The lower cytotoxicity of C1 –C4 compared to cisplatin is explained based on nucleotide excision repair mechanism. Abstract :